2014
DOI: 10.1002/jat.3059
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to MnCl2 · 4H2O during development induces activation of microglial and perivascular macrophage populations in the hippocampal dentate gyrus of rats

Abstract: Developmental exposure to Mn caused Mn accumulation in the brain tissue and transient disruption of granule cell neurogenesis, targeting the late stage differentiation of progenitor cells in the subgranular zone of the hippocampal dentate gyrus of rats. Because neurogenesis is influenced by proinflammatory responses, this study was performed to determine whether Mn exposure causes microglial activation in the dentate hilus, a region anatomically close to the subgranular zone of the dentate gyrus. Pregnant rats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Mn exposure has been suggested to cause microglial activation via various inflammatory pathways (Abe et al, 2015;Verina et al, 2011;Zhao et al, 2009). Our previous study has confirmed that Mn exposure increases the number of newly born microglial cells in the adult SVZ; however, this increase is mild but not substantial so that it does not contribute significantly to the overall cell proliferation in the SVZ under Mn influence (Fu et al, 2015a).…”
Section: Resultssupporting
confidence: 59%
“…Mn exposure has been suggested to cause microglial activation via various inflammatory pathways (Abe et al, 2015;Verina et al, 2011;Zhao et al, 2009). Our previous study has confirmed that Mn exposure increases the number of newly born microglial cells in the adult SVZ; however, this increase is mild but not substantial so that it does not contribute significantly to the overall cell proliferation in the SVZ under Mn influence (Fu et al, 2015a).…”
Section: Resultssupporting
confidence: 59%
“…Using the same dosing paradigm, the same group investigated epigenetic changes relevant to neurogenesis during and after Mn exposure and found changes in genes related to neurogenesis, including Mid1, Atp1a3,Nr2f1, and Pvalb 73 . In further studies, the same group observed activation of microglia and perivascular macrophages in the hippocampal dentate hilus, adjacent to the dentate gyrus, postulating that inflammation in involved in the changes in neurogenesis observed in their previous studies 74 . In an intrapersonal injection model of Mn exposure at 6 mg/kg in adult rats, copper levels, which are normally high in the subgranular zone, were reduced, while expression of the divalent metal transporter (DMT1), which transports both copper and Mn, was increased in the region 75 .…”
Section: Introductionmentioning
confidence: 93%
“…Once environmental exotoxins excessively activate microglia, the balance between its protection and pro-inflammatory effects is interrupted [12]. Significantly, excessive Mn exposure or its combination with lipopolysaccharide (LPS) may induce the activation of microglial cells, which then causes neuroinflammation via promoting the secretion of cytotoxic mediators, such as interleukin-1β (IL-1β) and reactive oxygen species (ROS) [13,14].…”
Section: Introductionmentioning
confidence: 99%